El mal uso de la acción de protección en el Ecuador - Ortiz Rivera, Ruth Cecilia (2015)
The act aims to investigate the development of new knowledge, and for any reason and must not deviate from the training process, so the National University of Loja, in accordance with the provisions of the Academic Regulations of the National System of Higher Education, It requires the student as a requirement for graduation at the professional level or undergraduate, present and sustain a job, called thesis or research, which is obtained after a steady process. To that end, and after getting the raw data or, in legal units and / or judged, he analyzed and defined, which has after several years of effectiveness of protective action, produced confusion. Protection Action, is set out in Art. 88 of the Constitution of the Republic of Ecuador and aims the direct and effective protection of the rights recognized in the constitution, and may be brought where there is only infringement of constitutional rights. That is, protective action is not appropriate when referring to aspects of pure legality, for which there are regular judicial channels. This legal guarantee is not an alternative means of justice, so it is up to the judge to determine whether there omission or violation of a right of action susceptible of protection; and, it forces the actor to attend this legal guarantee only if it considers that they have violated a constitutional right. With the above, specifically, the need to solve a problem of reality, through data collection, analysis and interpretation of these fundamentals, demonstration and presentation of results.